Targeting PIM1-Mediated Metabolism in Myeloid Suppressor Cells to Treat Cancer - Xin, Gang; Chen, Yao; Topchyan, Paytsar; Kasmani, Moujtaba Y; Burns, Robert; Volberding, Peter J; Wu, Xiaopeng; Cohn, Alexandra; Chen, Yiliang; Lin, Chien-Wei; Ho, Ping-Chih; Silverstein, Roy; et al. (Cancer immunology research, 2021)
There is a strong correlation between myeloid-derived suppressor cells (MDSC) and resistance to immune checkpoint blockade (ICB), but the detailed mechanisms underlying this correlation are largely unknown. Using single-cell RNA sequencing analysis in a bilateral tumor model, we found that immunosuppressive myeloid cells with characteristics of fatty acid oxidative metabolism dominate the immune-cell landscape in ICB-resistant subjects. In addition, we uncovered a previously underappreciated role of a serine/threonine kinase, PIM1, in regulating lipid oxidative metabolism via PPARγ-mediated activities. Enforced PPARγ expression sufficiently rescued metabolic and functional defects of MDSCs. Consistent with this, pharmacologic inhibition of PIM kinase by AZD1208 treatment significantly disrupted the myeloid cell-mediated immunosuppressive microenvironment and unleashed CD8 T-cell-mediated antitumor immunity, which enhanced PD-L1 blockade in preclinical cancer models. PIM kinase inhibition also sensitized nonresponders to PD-L1 blockade by selectively targeting suppressive myeloid cells. Overall, we have identified PIM1 as a metabolic modulator in MDSCs that is associated with ICB resistance and can be therapeutically targeted to overcome ICB resistance.